Correlation between shapes and sizes of dentofacial arches and their stable parameters - E. G. Vedeshina; D. A. Domenyuk; S. V. Dmitrienko (Кубанский научный медицинский вестник, 2016)
The study proposed an algorithm for determining the optimised predicted individual parameters of dental arches in people with abnormal shapes and sizes of dentofacial arches. The algorithm is based on the most stable parameters of the dental arches, namely the width of the dental arches measured between the second permanent molars and the sum of mesial-distal sizes of 14 permanent teeth. Reasonable calculation of linear dimensions based on the proposed stable parameters of the dental arches should be used in orthodontic treatment tactics development.